Patient Refusal of Care: Balancing Patient Autonomy and Professional Ethical Duties - Yusrita Zolkefli (Iran University of Medical Sciences, 2024)
Patient refusal of care often puts healthcare professionals in an ethical dilemma. The ethics of refusing nursing care are examined in this editorial, which emphasizes the patient's autonomy and the healthcare professional's duty to provide care. Coercion and information manipulation to override patient's refusal contradict principles of autonomy and justice. Through ethical analysis and case examples of assisting post-operative patients with early ambulation, it is clear that an excessive focus on patient's autonomy and the duty to provide care could jeopardize ethical practice.